Mobile Learning: Perspectives on Practice and Policy - Herro, Danielle; Arafeh, Sousan; Ling, Richard Seyler; Holden, Chris (Information Age Publishing, Inc., 2018)
Keywords: Mobile communication systems in education; United States; United States; Internet in education; dept.edl; faculty_collection

Preparing perform and impact ready school leaders for improving urban school success - Yavuz, Olcay; Gülmez, Gülçin (Research in Educational Administration & Leadership, 2018)
In an effort to develop and support high quality urban school leaders, this study examined what factors affect pre-service urban school leaders’ perception of preparedness for performing instructional leadership activities. The findings revealed that participating in a leadership training program is the only significant factor that predicts urban educators’ scores on instructional leadership readiness measures. By examining perception of preparedness of aspiring urban school leaders the findings contribute to our understanding about some perspectives to prepare and develop urban school leaders solve large and complex problems related to the curriculum, instruction and assessment. Implications for preparing performance ready school leaders in high need urban schools are further discussed. © Official Publication of EARDA-Turkish Educational Administration Research and Development Association.
0 citations (Crossref) [2023-10-31]
Keywords: Leadership training; Perception of preparedness; Urban leadership; dept.edl; peer-reviewed

School leadership training: Are we preparing future talent managers? - Yavuz, Olcay; Madonia, Peter; Abolafia, Victoria M. (Uluslararası Liderlik Eğitimi Dergisi, 2018)
Effective leadrship talent management practices are important components of successful organizations. This correlational quantitative study is designed to inform educational leadership training programs in their work to revise their curricula and to utilize the candidates’ perception data to ensure successful program delivery and outcomes. Particularly, the findings of this study aim to inform educational leadership preparation practices on developing talent managers who can recruit, hire, retain, and support the most talented and high qualified teachers, as well as support staff available in the education job market. Results indicate that after completing the first year of educational leadership training only around half of the aspiring school leaders felt performance or impact ready to serve as talent managers, in order to select and develop highly qualified educators to increase the success of all students. The findings also suggest the importance of understanding how various factors predict an individual’s perception of preparedness to perform talent management leadership activities. Therefore, the study results may serve to enrich conversations of educational leadership training programs, guide program evaluation efforts, and help ensure candidates in educational leadership programs are exposed to talent management and strategies in their coursework. This may help future school leaders clearly and purposefully apply their knowledge and skills.
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Perceptions of social emotional learning needs in high poverty schools - Generali, Margaret M.; Yavuz, Olcay; Parzych, Jennifer (Journal of Contemporary Administrative Science, 2018)
This paper explores the perceived social emotional learning needs of students in high poverty schools. Social emotional learning (SEL)is recognized within the literature as critical to success in school and in life. Emergingwork supports the acquisition of a SEL skillset within grades kindergarten through twelve ( K-12) schools. This survey examines the perceptions of social emotional needs as reported by students, parents and school faculty members across four different high poverty schools in the USA. Findings provide effective strategies and valuable data for school leaders, educators, and counselors in addressing the social emotional needs of urban students.
Keywords: dept.csp; dept.edl; peer-reviewed; ⛔ No DOI found

Urban tween talk about using mobile phones for learning - Arafeh, Sousan; Kuszpa, M; Weller, M; Mitchell, T (Mobile Learning: Perspectives on Practice and Policy, 2018)
There can be no doubt that mobile technologies are here to stay. Global mobile traffic grew 74 percent in 2015 alone, with 563 million devices and connections added – most of them tablets and Smartphones. This growth has been 4000-fold in the past 10 years and 400 million-fold in the past 15 years (Cisco, 2016). Mobile technologies permeate the lives of 21st century citizens as mainstays of organizational and institutional day-to-day operations, commerce, and communication and as tools used to support individuals' personal, social, and career responsibilities. In both the corporate and educational worlds, e- and m-learning and marketing with mobile technologies are moving forward at breakneck speed with, in many cases, a blurring of traditional sector boundaries. As neither the technology nor the uses are static, exploring practices and policies that underpin this quickly shifting mobile technology context is crucial for ensuring its intelligent, purposeful, and equitable use. This edited book provides a venue for researchers to share their work on mobile learning with a focus on uses for mobiles in informal settings and PK-20 classrooms, language learning, mobile gaming, leadership and policy issues, and what mobile learning in the future may be. It assists researchers and educators to consider and answer questions such as: What is "mobilelearning" today How can mobiles be used to enable learning How is mobile learning crossing or connecting economic, social, and/or cultural sectors How do specific cultural practices with media influence mobile learning (e.g
Keywords: dept.edl

Access versus success: Services for students with disabilities in postsecondary education. - Sassu, Kari (Journal of Educational Leadership and Policy Studies, 2018)
Keywords: dept.csp; peer-reviewed; ⛔ No DOI found

Attitudinal instrument development: Assessing cognitive, affective, and behavioral domains of teacher attitudes toward teaching all students - Gregory, Jess L; Noto, Lori A (Cogent Education, 2018)
Despite their entree into the physical space of general education classrooms and the expected instruction of the core academic standards, students with disabilities may still be excluded. Successful inclusion requires a commitment at district, school and classroom level. The attitude of the general education teacher toward the inclusion of students with disabilities is a critical component in the success of inclusionary efforts. The attitudes toward teaching all students (ATTAS-mm) instrument are a nine-item scale with strong reliability and validity that measures educator attitudes. The three subscales: believing all students can succeed in general education classrooms (cognitive), developing personal and professional relationships (affective), and creating an accepting environment for all students to learn (behavioral) explain nearly 80% of the variance in scores. The unstandardized Cronbach alpha for the entire ATTAS-mm scale was 0.83. The three subscales also demonstrated acceptable reliability values (Cognitive, 0.72; Affective, 0.93; Behavioral, 0.84). With strong internal reliability and validity established through a panel of experts and alignment with cognitive psychology literature, the ATTAS-mm was determined to be a valid and reliable instrument for measuring the attitudes toward teaching all students. © 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/178-902-357-221-200 tex.type: [object Object]
Keywords: ATTAS-mm; dept.edl; inclusion; instrument development; peer-reviewed; special education; teacher attitudes